The Role of Management in the Development of Culture and Art - Erejepaevna, Seydullaeva Bibiayim (Research Parks Publishing LLC, 2023)
This article contains analytical comments about the role and importance of management in the field of culture and art. In particular, scientific research was conducted on the activities of culture and art institutions and the activities of leaders in these processes. Also, suggestions and recommendations are given for the development of management in the further improvement of cultural management.